2009
DOI: 10.1177/0269216309103124
|View full text |Cite
|
Sign up to set email alerts
|

Ratings of symptoms and comfort in dementia patients at the end of life: comparison of nurses and families

Abstract: After-death reporting by proxies on end-of-life outcomes is used in research and can also be used to target institutions directly to improve practice. We compared the scores of family caregivers and nurses on two End-of-Life in Dementia Scales (EOLD) scales: Symptom Management (SM; range 0-45) over the last 3 months of life and Comfort Assessment in Dying (CAD; range 14-42). Higher scores represent better outcomes. Four Dutch nursing homes retrospectively enrolled 48 decedents with dementia. Total mean scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…In addition to pain and shortness of breath, US and Dutch families and Dutch nurses also reported that dementia patients experienced discomfort, restlessness, and difficulty swallowing more than other symptoms [53,54]. Agitation is a symptom which is less frequently assessed in studies on the last phase of life, but may be as common as pain and shortness of breath [28,34,44,53,54].…”
Section: Symptoms and Treatment At The End Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to pain and shortness of breath, US and Dutch families and Dutch nurses also reported that dementia patients experienced discomfort, restlessness, and difficulty swallowing more than other symptoms [53,54]. Agitation is a symptom which is less frequently assessed in studies on the last phase of life, but may be as common as pain and shortness of breath [28,34,44,53,54].…”
Section: Symptoms and Treatment At The End Of Lifementioning
confidence: 99%
“…Agitation is a symptom which is less frequently assessed in studies on the last phase of life, but may be as common as pain and shortness of breath [28,34,44,53,54]. One study found that psychiatric symptoms such as agitation and depression were less bothersome to family members than pain, breathing problems, and memory loss [46].…”
Section: Symptoms and Treatment At The End Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41] Where the views and experiences of family carers have been sought, it is usually to evaluate quality of life, quality of death and proxy views regarding a good death, on behalf of their relative, post-bereavement. 20,[42][43][44][45] Rarely have the views and experiences of family caregivers in their own right been elicited.…”
mentioning
confidence: 99%
“…3 Patients with advanced dementia frequently cannot verbalize their needs; proxies may assess quality of dying and end-of-life care including families' satisfaction, which requires specific instruments. [4][5][6] Selecting the optimal observational study design to describe end-of-life experiences and factors associated with end-of-life outcomes involves choosing either between collection of data both before and after death (prospectively; "cohort study") or after death exclusively (retrospectively on decedents; "case series," or "mortality follow-back" 7,8 design).…”
mentioning
confidence: 99%